The Effect of a Training Program to Develop Speed Endurance and (YOYO) Test for Football Referees Level 2 - Abd, Kadgim; Kadhim, Ahmed (Journal of Physical Education, 2016)
The problem of this study comes as a result to the need of new updated trainingprogram to help football referees developing a high level of fitness during matches. Refereesare expected to be physically well prepared in order to endure long time matches withcontinuous running in up and down speed. However, they are still randomly prepared basedon their own potentials and general information in Training Science. Hence the need todouble the efforts and set new training program to help passing the new referees’ (Yoyo) testupdated by the International and the Asian Federation. The researcher has used theexperimental method of one group style. The subject includes (15) football referees (level 2)out of (25) rated 60% of the original community. The tests used are (shuttle running 25x8),(30 m speed), and (YOYO) test. The conclusions have confirmed the positive role of thetraining program: 1) on the development process and the improvement of the referees’physical abilities (speed and speed endurance); 2) on passing (YOYO) tests for almost all thereferees.The researcher finally has recommended: 1) the central Referees Committee in IraqiFederation to depend on specialized coaches in training or fitness. 2) to conduct regulartraining whether weekly or (3-4) times per week to raise the physical abilities of the referees